2020
DOI: 10.1016/j.xjon.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation transcatheter aortic valve implantation

Abstract: Objective: Transcatheter aortic valve implantation (TAVI) procedures are increasing rapidly, but the durability of tissue valve and periprocedural complications are not satisfactory. Immune reaction to the galactose-a-1,3 galactose b-1,4-N-acetylglucosamine (a-Gal) and conventional processing protocols of cardiac xenografts lead to calcification. Next-generation TAVI needs to be made with a-Gal-free xenografts by multiple anticalcification therapies to avoid immune rejection and enhance durability, and three-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The in vivo performance of the valves following the TAVI was exemplary, with proper stent fitting, outstanding coronary flow, better hemodynamic profile, and improved aortic valve function. Importantly, the study by Lim and colleagues 7 is well appreciated for the minimal α-Gal–triggered immune reaction and calcification over the 8-month period. In addition, the findings in a clinically relevant large animal model could be translated to humans.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The in vivo performance of the valves following the TAVI was exemplary, with proper stent fitting, outstanding coronary flow, better hemodynamic profile, and improved aortic valve function. Importantly, the study by Lim and colleagues 7 is well appreciated for the minimal α-Gal–triggered immune reaction and calcification over the 8-month period. In addition, the findings in a clinically relevant large animal model could be translated to humans.…”
mentioning
confidence: 99%
“…In this context, Lim and coinvestigators 7 in the current issue of the Journal demonstrated a promising strategy to address the immunogenicity of α-Gal and subsequent calcification in porcine TAVI using a multidisciplinary approach of decellularization, use of immunologically modified α-galactosidase, and 3-dimensional printing technology in their TAVI-sheep model. This evolving technology is schematically shown in Figure 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation